2017
DOI: 10.3389/fpls.2017.00220
|View full text |Cite
|
Sign up to set email alerts
|

Cyanogen Metabolism in Cassava Roots: Impact on Protein Synthesis and Root Development

Abstract: Cassava (Manihot esculenta Crantz), a staple crop for millions of sub-Saharan Africans, contains high levels of cyanogenic glycosides which protect it against herbivory. However, cyanogens have also been proposed to play a role in nitrogen transport from leaves to roots. Consistent with this hypothesis, analyses of the distribution and activities of enzymes involved in cyanide metabolism provides evidence for cyanide assimilation, derived from linamarin, into amino acids in cassava roots. Both β-cyanoalanine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 64 publications
3
17
0
Order By: Relevance
“…With reference to cassava plant, the use of biotechnology involves the exploitation of biological processes, especially the genetic manipulation of microorganisms for the production of hormones and enzymes, and manipulation of genes with the aim of producing disease-resistant varieties, improving the nutrient composition, as well as eliminating any ANF inherent in cassava crop. Several studies have shown the efficacy of biotechnologically targeted processing methods in improving the feed value of cassava for both humans and animals, for instance, in a study to ascertain the feasibility of enhancing root cyanide assimilation into protein, optimally overexpressed Arabidopsis CAS and NIT4 genes in cassava roots resulted in up to a 50% increase in root total amino acids and a 9% increase in root protein accumulation [88]. It has been hypothesised that cyanogen toxicity in cassava foods can be accelerated by cyanogenesis and cyanide volatilization during food processing [89].…”
Section: Modern Processing Methodsmentioning
confidence: 99%
“…With reference to cassava plant, the use of biotechnology involves the exploitation of biological processes, especially the genetic manipulation of microorganisms for the production of hormones and enzymes, and manipulation of genes with the aim of producing disease-resistant varieties, improving the nutrient composition, as well as eliminating any ANF inherent in cassava crop. Several studies have shown the efficacy of biotechnologically targeted processing methods in improving the feed value of cassava for both humans and animals, for instance, in a study to ascertain the feasibility of enhancing root cyanide assimilation into protein, optimally overexpressed Arabidopsis CAS and NIT4 genes in cassava roots resulted in up to a 50% increase in root total amino acids and a 9% increase in root protein accumulation [88]. It has been hypothesised that cyanogen toxicity in cassava foods can be accelerated by cyanogenesis and cyanide volatilization during food processing [89].…”
Section: Modern Processing Methodsmentioning
confidence: 99%
“…Hydrogen cyanide (HCN) is a gaseous acid produced in nature by a wide variety of microorganisms such as fungi, bacteria, and algae (Knowles, 1976), as well as in cyanogenic plant food such as almonds (Prunus dulcis), millet sprouts (Panicum miliaceum), cassava roots (Manihot esculenta), or lima beans (Phaseolus lunatus), which are capable of accumulating significant amounts of cyanide, produced by the hydrolysis of cyanogenic glycosides (Hanschen et al, 2014;Baskar et al, 2016;Zidenga et al, 2017). Noncyanogenic plant species also produce cyanide as a byproduct of some metabolic processes, such as during camalexin and ethylene biosynthesis (Peiser et al, 1984;Yip and Yang, 1988;Böttcher et al, 2009).…”
mentioning
confidence: 99%
“…Several methods are used for the quantitative determination of anti-nutritional factors in foods based on reports by different authors. These are: trypsin inhibitor activities are determined according to these studies [6,15,17,[25][26][27][28].…”
Section: Methods For Quantification Of the Anti-nutritional Factors Imentioning
confidence: 99%
“…The bioavailability of the essential nutrients in plant foods could be reduced by the presence in these plants of some anti-nutritional factors such as oxalates and cyanogenic glycosides [28]. Too much of soluble oxalate in the body prevents the absorption of soluble calcium ions as the oxalate binds the calcium ions to form insoluble calcium oxalate complexes.…”
Section: Biochemical Effects Of the Anti-nutritional Factorsmentioning
confidence: 99%
See 1 more Smart Citation